Solar Bubble Dryer, a mobile and low-cost drying technology for rice - CGIAR Research Program on Rice (2020)
The SBD was developed in a consortium consisting of IRRI, GrainPro and the University of Hohenheim. It has been commercial released in 2014 and is being sold by GrainPro world-wide.